Influence of vanadium addition on corrosion behavior of high‐energy ball milled aluminum alloy 2024. Issue 2 (25th September 2022) - Ozdemir, Furkan; Gupta, Rajeev K.
Abstract: The effect of V addition on the hardness and corrosion of aluminum alloy 2024 (AA2024) produced by high‐energy ball milling has been investigated. High‐energy ball milled alloys exhibited enhanced solid solubility of alloying elements and ultrafine grains. The addition of V improved the corrosion resistance of the AA2024 alloy, which was attributed to the deposition of V on the cathodic particles and therefore decrease in their ability to sustain large cathodic currents. Abstract : The influence of vanadium addition on the corrosion behavior of AA2024 is investigated using electrochemical and immersion tests. The electrochemical tests exhibited that V containing nanocrystalline AA2024 demonstrated the ability to repassivate, which was attributed to the deposition of V on cathodic particles and the subsequent decrease in cathodic reaction kinetics.